Influence Perceived Ease of Use, Perceived Usefulness and Social Influence Against Intention to Use Video on Demand Services at Netflix - Sari, Tri Novita; Purnamasari, Femei; Nurmalia, Gustika (Indonesian Journal of Islamic Economics and Finance, 2025)
As the number of users of Video on Demand services such as Netflix continues to grow, interest in examining the factors that influence the intention to use these platforms is also increasing. This inquiry aims to explore consumer behavior toward such services from the perspective of Islamic Economics and to analyze the effects of perceived usefulness, perceived ease of use, and social influence on the intention to use Netflix among residents of Sukarame, Bandar Lampung. A quantitative approach was employed, using purposive sampling to select 96 respondents. The data were analyzed using the Structural Equation Modeling Partial Least Square method. The discoveries indicate that all three independent element s perceived usefulness, ease of use, and social influence have a positive and significant impact on the intention to use Netflix. These outcomes can serve as a valuable reference for service providers seeking to improve user experience and for scholars conducting further research on technology adoption within an Islamic framework.